2013
DOI: 10.1186/1757-1146-6-28
|View full text |Cite
|
Sign up to set email alerts
|

The effect of shoe toe box shape and volume on forefoot interdigital and plantar pressures in healthy females

Abstract: BackgroundIll-fitting footwear can be detrimental to foot health with the forefoot being an area for most discomfort. Studies on footwear have primarily examined sports or orthopaedic prescription shoes and little is known about the effects that everyday flat shoes have on the forefoot. The aim of this study was to investigate the effect of toe box shape in a popular slip-on pump on dorsal and plantar pressures with particular interest around the forefoot in a healthy female population.MethodA convenience samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 35 publications
0
34
0
Order By: Relevance
“…Recent research has found that footwear‐related pain is highly prevalent among women in the general population and that there is a strong association between foot pain and ill‐fitting footwear . Moreover, footwear choices among younger women are driven predominantly by fashion and the self‐image they want to portray .…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has found that footwear‐related pain is highly prevalent among women in the general population and that there is a strong association between foot pain and ill‐fitting footwear . Moreover, footwear choices among younger women are driven predominantly by fashion and the self‐image they want to portray .…”
Section: Discussionmentioning
confidence: 99%
“…Aspects related to the upper of the footwear would also be expected to affect reported comfort of wearers and biomechanical outcomes. In women's dress shoes, the toe-box shape has been demonstrated to alter plantar and inter-digital pressures (Branthwaite, Chockalingam, & Greenhalgh, 2013). The volume of a shoe upper has also been implicated as a risk factor for reduced foot health and pain when wearing medical-grade footwear (Hurst, Branthwaite, Greenhalgh and Chockalingham, 2017), which is a function of both upper shape and material.…”
Section: Introductionmentioning
confidence: 99%
“…Biomechanical studies have revealed that heel elevation increases the pressures under the metatarsal heads (8), limits motion of the first metatarsophalangeal joint (9), and increases the stiffness of the Achilles tendon (10), whereas shoes with a narrow toe box increase pressures on the medial side of the foot and between the toes (11). Over time, these changes may contribute to the development of foot pain and deformity.…”
mentioning
confidence: 99%